2016
DOI: 10.1007/s00204-016-1678-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effect levels of regulatory studies with endpoints derived in targeted anti-androgenic studies: example prochloraz

Abstract: Prochloraz is an imidazole fungicide, and its regulatory toxicological data package has been primarily generated in the 1990s. More recently, studies have been published demonstrating an interaction with hormone receptors/steroidogenesis and effects with an endocrine mode of action. In the present study, prochloraz has been investigated in a comprehensive in vivo study including relevant elements of current regulatory reproduction toxicity studies and additional mechanistic parameters. Prochloraz was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Regarding reproductive effects, prochloraz exposure can induce nipple retention in male offspring (Christiansen et al 2009;Vinggaard et al 2005), whereas effects on AGD are conflicting between studies. If taking birth-weight into account, there were no significant effects on male AGD at doses similar to those causing nipple retention (25-150 mg/kg) (Christiansen et al 2009;Melching-Kollmuss et al 2017;Noriega et al 2005;Vinggaard et al 2005). Another study reported around 10% shorter male AGD after fetal exposure to high doses of prochloraz concomitant with nipple retention at the same doses (Laier et al 2006).…”
Section: Agd In Animal Toxicity Studies: Miscellaneous Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding reproductive effects, prochloraz exposure can induce nipple retention in male offspring (Christiansen et al 2009;Vinggaard et al 2005), whereas effects on AGD are conflicting between studies. If taking birth-weight into account, there were no significant effects on male AGD at doses similar to those causing nipple retention (25-150 mg/kg) (Christiansen et al 2009;Melching-Kollmuss et al 2017;Noriega et al 2005;Vinggaard et al 2005). Another study reported around 10% shorter male AGD after fetal exposure to high doses of prochloraz concomitant with nipple retention at the same doses (Laier et al 2006).…”
Section: Agd In Animal Toxicity Studies: Miscellaneous Compoundsmentioning
confidence: 98%
“…Female rats exposed to the azole fungicide prochloraz present with longer AGD at birth, concomitant with elevated progesterone levels (Laier et al 2006;Melching-Kollmuss et al 2017). Prochloraz can induce progesterone synthesis in vitro by CYP17 inhibition at concentrations above 10 nM (Dreisig et al 2013), a mechanism confirmed in vivo, where fetal plasma concentrations were measured at 24 nM following maternal exposure to 150 mg/kg bw/day of prochloraz (Laier et al 2006).…”
mentioning
confidence: 97%
“…A minor change in the concentration of an endocrine disrupting chemical can induce significant changes in biological endpoints even though the dose is small (Futran Fuhrman et al 2015). Currently, risk assessment methodologies do not sufficiently assess the hazard associated with low-dose exposure to endocrine active substances (Melching-Kollmuss et al 2017) and the lack of a universal definition for "low dose" is one obstacle to this.…”
Section: Discussionmentioning
confidence: 99%
“…The mixtures data reported in this investigation were captured in the final of a series of three separate experiments of the same study design addressing the theme of single and mixed exposures to low dose levels of anti-androgens. Since we have previously published the effects of the single-substance exposures to the three test substances in prior reports (Fussell et al 2015 ; Melching-Kollmuss et al 2017 ; Flick et al 2016 ), these outcomes will not be discussed here in detail. Instead, the included single-substance exposure data are presented only for the purposes of comparison to the mixed exposures tested in this specific investigation and will be discussed only in this context.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the single compound testing have been published previously, i.e. flutamide (Fussell et al 2015 ), prochloraz (Melching-Kollmuss et al 2017 ) and vinclozolin (Flick et al 2016 ). Here we report on the effects of combined exposure to all three anti-androgens.…”
Section: Introductionmentioning
confidence: 99%